Mobilizing Citizens at Their Level: A Case Study of Public Engagement - Charu Uppal (Journalism Practice, 2021)
Mobilizing information (MI), defined as ‘information that allows the public to act,’ is often omitted in news stories because it is considered partisan. Without relevant MI in media, participation in public discourse is restricted to the politically aware, i.e., to politicians, interest groups, and activists. This paper argues that Lemert’s definition of MI is limited and does not consider building upon audience’ orientation. Applying a more complex form of MI identified earlier (study, author) that takes audience orientation into account, to a television talk show, the paper demonstrates how varying levels of MI may be utilized. Depending on audience orientation, MI can be either invitational or empowering. More specifically, the three types of invitational MI, in ascending order of their mobilizing potential, are motivational, informational, and purposive. MI’s (author, year) application is illustrated through one episode of Satyamev Jayate (SMJ), an Indian talk show, to demonstrate how MI may be directed at citizens with different levels of political orientation. SMJ has successfully engaged the public by adeptly bringing together interactive technologies, and journalistic methods. This paper also introduces the concept of “mobilizing context”.